Collaborative Governance Dalam Memajukan Kebudayaan Bali Melalui Pola Pembangunan Semesta Berencana Menuju Bali Era Baru di Kota Denpasar - I Ketut Wahyu Wijaya; Kadek Wiwin Dwi Wismayanti; Komang Adi Sastra Wijaya (CV. Lenggogeni Data Publishing, 2023)
ABSTRACT The strengthening and promotion of Balinese Culture in the City of Denpasar is manifested in the form of policies to achieve the goals set through the Regional Development Vision of Bali Nangun Sat Kerthi Loka Bali which is realized by creating a collaborative governance. The collaboration that took place to achieve this goal was carried out by several collaborators, namely from the government sector (Denpasar City Culture Office, Denpasar City Tourism Office, and Denpasar City Traditional Village Council); private sector (Naluri Manca); and community owners of MSMEs in Denpasar City. By carrying out good collaboration management, the objectives of the related collaboration above are expected to be able to create strengthening and promotion of culture in the city of Denpasar itself. This study aims to find out how the implementation of collaborative governance in advancing Balinese culture in the city of Denpasar. This research uses descriptive qualitative method with data collection techniques in the form of observation, interviews, and documentation. The results of this study indicate that collaborative governance that is running in advancing Balinese culture in the city of Denpasar is still not maximal in fulfilling the indicators or criteria for the success of a collaboration. This can be seen from the eight indicators used, only four indicators are able to be fulfilled by the ongoing collaboration, where this collaboration has not been able to meet the indicators of network structure, governance, trust among the participants, and access to resources.